Endothelial AT(1) and AT(2) pathways in aortic responses to angiotensin II after stress and ethanol consumption in rats - Ferreira Baptista, Rafaela de Fatima [UNESP]; Chies, Agnaldo Bruno [UNESP]; Taipeiro, Elane de Fatima; Cordellini, Sandra [UNESP] (Informa Healthcare, 2014)
Stress and ethanol are important cardiovascular risk factors. Their vascular and blood pressure (BP) effects were evaluated alone and in combination. Adult male Wistar rats (8-10 per group) were separated into control, ethanol (ethanol 20% in drinking water for 6 weeks), stress (restraint 1 h/d 5 d/week for 6 weeks), and ethanol/stress (in combination) groups. Systolic BP was evaluated weekly. Concentration-response curves for contractile responses to angiotensin II in the absence and the presence of losartan (AT(1)-blocker), PD123-319 (AT(2)-blocker), L-NAME (nitric oxide synthase inhibitor), or indomethacin (cyclooxygenase inhibitor) were obtained in isolated intact and endothelium-denuded aortas. Effective concentration 50% (EC50) and maximum response (MR) were compared among groups using MANOVA/Tukey tests. Stress and stress plus ethanol increased BP. Ethanol and stress, alone and in combination, did not alter angiotensin responses of intact aortas. PD123-319 decreased MR to angiotensin II in intact aortas from the ethanol and ethanol/stress groups relative to control in the presence of PD123-319. Losartan increased MR to angiotensin II in intact aortas from the stress and ethanol/stress groups relative to control in the presence of losartan. None of the protocols altered angiotensin responses of denuded aortas. Neither indomethacin nor L-NAME altered angiotensin responses of intact aortas from the experimental groups. Thus ethanol and ethanol plus stress may alter endothelial signaling via AT(1)-receptors, without changing systemic BP. Stress and stress plus ethanol may alter endothelial signaling via AT(2)-receptors, and thereby increase BP. Knowledge of such vascular changes induced by stress and/or ethanol may contribute to understanding adverse cardiovascular effects of stress and ethanol consumption in humans.
Keywords: Angiotensin II; AT(1) and AT(2) pathways; ethanol consumption; nitric oxide; restraint stress; vascular reactivity